2020
DOI: 10.1074/jbc.ra120.013281
|View full text |Cite
|
Sign up to set email alerts
|

The HCN domain is required for HCN channel cell-surface expression and couples voltage- and cAMP-dependent gating mechanisms

Abstract: Hyperpolarization-activated cyclic nucleotide-gated (HCN) channels are major regulators of synaptic plasticity and rhythmic activity in the heart and brain. Opening of HCN channels requires membrane hyperpolarization and is further facilitated by intracellular cyclic nucleotides (cNMPs). In HCN channels, membrane hyperpolarization is sensed by the membrane-spanning voltage sensor domain (VSD), and the cNMP-dependent gating is mediated by the intracellular cyclic nucleotide-binding domain (CNBD) connected to th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 42 publications
5
31
0
Order By: Relevance
“…In summary, opposite subunits in HCN channels are functionally coupled. Our data suggest that the interactions between opposite subunits, embedded in a network of interactions between adjacent subunits 15 , 16 , are relevant for the autoinhibitory properties of the channels. Both cAMP binding and charge inversion of a single amino acid drive the channel into a conformation that weakens autoinhibition.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In summary, opposite subunits in HCN channels are functionally coupled. Our data suggest that the interactions between opposite subunits, embedded in a network of interactions between adjacent subunits 15 , 16 , are relevant for the autoinhibitory properties of the channels. Both cAMP binding and charge inversion of a single amino acid drive the channel into a conformation that weakens autoinhibition.…”
Section: Discussionmentioning
confidence: 78%
“…Different techniques, including electrophysiological approaches, fluorescence microscopy, and cryo-electron microscopy combined with mutagenesis were used to show intensive interactions between neighboring subunits: S4-S5 linker-CL interactions 6 , 11 , CL-CL interactions 12 14 , CNBD-CNBD interactions 6 , 12 , and very recently interactions between the newly discovered HCN domain with the CNBD, the voltage-sensing domain, and the CL region 6 , 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…The V240 residue is actually located in the HCNc α-helix. The HCND could act as a sliding crank that converts the planar rotational movement of the CNBD into a rotational upward displacement of the VSD mechanically coupling thus, the CNBD and the VSD (Porro et al, 2019; Wang et al, 2020). HCND normally keeps the VSD in a position, which is unfavorable for channel opening (Porro et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, it has been revealed that the hyperpolarization-activated cyclic nucleotide-gated cation channel (HCN) is a voltage-gated ion channel that works in a time-dependent manner [ 40 , 41 ]. The HCN channels consist of 4 subunits (HCN1–4).…”
Section: Discussionmentioning
confidence: 99%